Research and design of a French for Specific Purposes course for Hotel and Tourism for students studying at the Hotel and Tourism Management department of CUT and for professionals of this sector. - Georgiadou, Olga (My University, 2026)
Research and design of a French for Specific Purposes course for Hotel and Tourism for students studying at the Hotel and Tourism Management department of CUT and for professionals of this sector.